Canadian environmental philosophy - DesRoches, C. Tyler, 1980-; Jankunis, Frank, 1983-; Williston, Byron, 1965- (McGill-Queen's University Press, 2019)
"Canadian Environmental Philosophy is the first collection of essays to take up theoretical and practical issues in environmental philosophy today, from a Canadian perspective. The essays cover various subjects, including ecological nationalism, the legacy of Grey Owl, the meaning of "outside" to Canadians, the paradigm shift from mechanism to ecology in our understanding of nature, the meaning and significance of the Anthropocene, the challenges of biodiversity protection in Canada, the conservation status of crossbred species in the age of climate change, and the moral status of ecosystems. This wide range of topics is as diverse and challenging as the Canadian landscape itself. Given the extent of humanity's current impact on the biosphere--especially evident with anthropogenic climate change and the ongoing mass extinction--it has never been more urgent for us to confront these environmental challenges as Canadian citizens and citizens of the world. Canadian Environmental Philosophy galvanizes this conversation from the perspective of this place."--